(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This informal workshop comprised the sharing of delegates’ early experiences of handling money together with more recent financial issues arising in the counselling room. Whilst some of those experiences are reproduced below [with delegates’ permission], this article sets out some general reflections about our relationship to money. At the start of the workshop delegates were given several pages of ’money’ quotes a selection of which are reproduced below.